Fluorescence of a benzothienopyridopyrimidone in solution and in lipid vesicles - Castanheira, Elisabete M. S. (2006)
Fluorescence properties of a biologically active benzothienopyridopyrimidone in solution and in lipid vesicles are reported. Assays at different pH values (0.5–10) allowed the determination of pKa = 2.0, showing that this compound may be useful as a pH indicator for pH ≤ 4. In lipid vesicles, benzothienopyridopyrimidone locates in a water-rich environment, indicating that it can be carried in the hydrophilic region of liposomes for drug delivery applications.